Revenue allocation and resource control in Nigerian federation - Nwokedi, Ralph Chiemeka (Enugu: Snaap Press Ltd., 2003)
This book provides an analysis of the various principles of revenue allocation and causes of controversy between the federal and state governments over revenue derivation and resource control with comments on relevant Supreme Court rulings and new proposals for equitable revenue sharing."
An analysis of various principles of revenue allocation and causes of controversy between the federal and state government over revenue derivation and equitable revenue sharing.
Includes Index.
lje 25/08/16, ijb 06/02/2018
Loans
Keywords: Intergovernmental fiscal relations; Fiscal policy; Revenue